2012
DOI: 10.1597/10-127.1
|View full text |Cite
|
Sign up to set email alerts
|

New Classification Scheme of Proboscis Lateralis Based on a Review of 50 Cases

Abstract: The redefined classification contains two new groups: group V as hypertelorism with encephalocele and group VI as hypotelorism. A new classification scheme is proposed as not only convenient for clinical application but also embryologically accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 41 publications
(48 reference statements)
0
29
1
Order By: Relevance
“…Proboscis Lateralis is a rare congenital deformity which has a sporadic nature 1 3 . Boo-Chai 4 , who particularly showed a male preponderance with no side preference, classified the condition into four: Group 1: Proboscis with normal nose and all other associated anomaly (rarest form) Group 2: Proboscis with only nasal deformity Group 3: Proboscis with nasal deformity and associated with a deformity of the eye, and/or its adnexa on the same side Group 4: Proboscis with defects in group 3, but is also associated with cleft lip and/or palate Another theory suggests that an imperfect fusion of the lateral nasal wall and maxillary processes leads to Proboscis Lateralis 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Proboscis Lateralis is a rare congenital deformity which has a sporadic nature 1 3 . Boo-Chai 4 , who particularly showed a male preponderance with no side preference, classified the condition into four: Group 1: Proboscis with normal nose and all other associated anomaly (rarest form) Group 2: Proboscis with only nasal deformity Group 3: Proboscis with nasal deformity and associated with a deformity of the eye, and/or its adnexa on the same side Group 4: Proboscis with defects in group 3, but is also associated with cleft lip and/or palate Another theory suggests that an imperfect fusion of the lateral nasal wall and maxillary processes leads to Proboscis Lateralis 5 .…”
Section: Discussionmentioning
confidence: 99%
“… Group IV: lateral proboscis with ipsilateral deformity of the nose, eye, and/or ocular adnexa, plus the cleft lip and/or palate. However, Sakamoto et al [ 7 ] proposed a new classification in 2012 following a review of 50 cases by adding 2 new groups to Boo-Chai's classification. Group V: lateral proboscis with encephalocele.…”
Section: Discussionmentioning
confidence: 99%
“…It may be unilateral or bilateral [ 3 , 5 , 6 ] with a 2 : 1 male-female preponderance [ 5 ]. According to Guerrero et al [ 1 ], it was first reported in 1861 by Forster in his monograph congenital malformations of the human body, while Boo-Chai [ 5 ] suggested a classification of this entity in 1985, and it was subsequently modified by Sakamoto et al [ 7 ] in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Teratoma is been reported to occur in 1:200,000 live births, of which 2% are craniofacial teratomas. One phenotype of craniofacial teratoma is proboscis lateralis, which can have both intracranial and extracranial malformations [ 11 , 12 ]. Craniofacial teratomas are usually diagnosed prenatally by routine fetal ultrasonography [ 2 , 8 ].…”
Section: Discussionmentioning
confidence: 99%